Generalized Solution of the First Boundary Value Problem for Parabolic Monge-Ampere Equation (Journal of Partial Differential Equations, 2001)
The existence and uniqueness of generalized solution to the first boundary value problem for parabolic Monge-Ampère equation - ut det D²_xu = f in Q = Ω × (0, T], u = φ on ∂_pQ are proved if there exists a strict generalized supersolution u_φ, where Ω ⊂ R^n is a bounded convex set, f is a nonnegative bounded measurable function defined on Q, φ ∈ C(∂_pQ), φ(x, 0) is a convex function in \overline{Ω}, ∀x_0 ∈ ∂Ω, φ(x_0, t) ∈ C^α([0, T]).